2007
DOI: 10.4049/jimmunol.179.4.2051
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The ST2 Ligand IL-33 Potently Activates and Drives Maturation of Human Mast Cells

Abstract: IL-33, the natural ligand of the IL-1 receptor family member ST2L, is known to enhance experimental allergic-type inflammatory responses by costimulating the production of cytokines from activated Th2 lymphocytes. Although ST2L has long been known to be expressed by mast cells, its role in their biology has not been explored. In this study we report that IL-33 directly stimulates primary human mast cells (MCs) to produce several proinflammatory cytokines and chemokines and also exerts a permissive effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
463
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 467 publications
(488 citation statements)
references
References 19 publications
18
463
0
3
Order By: Relevance
“…5 In addition, IL-33 has been shown to promote the maturation and survival of human mast cells and to induce their secretion of cytokines IL-5 and IL-13, which promote the survival and effector functions of eosinophils. 6,7 Together with the results from mouse models, 1,3,4 these results indicate that IL-33 might play a pivotal role in the exacerbation of allergic inflammation in allergic diseases mediated by the activation of eosinophils.…”
Section: Introductionmentioning
confidence: 66%
“…5 In addition, IL-33 has been shown to promote the maturation and survival of human mast cells and to induce their secretion of cytokines IL-5 and IL-13, which promote the survival and effector functions of eosinophils. 6,7 Together with the results from mouse models, 1,3,4 these results indicate that IL-33 might play a pivotal role in the exacerbation of allergic inflammation in allergic diseases mediated by the activation of eosinophils.…”
Section: Introductionmentioning
confidence: 66%
“…Although the dermal cells responsible for recruiting neutrophils following UVB exposure are not known, studies using mast cell deficient mice show that mast cells are critical cellular intermediaries required for the recruitment of neutrophils to sites of inflammation. 84 While direct exposure of cord blood derived mast cells to UVB in vitro causes CXCL8 production in these cells, 85 this is unlikely to be the primary mechanism by which dermal mast cells produce CXCL8 after UV exposure in vivo; rather, we hypothesize that UVB-induced PAF stimulates IL-33 production in fibroblasts that then acts either in an autocrine manner 86 or on neighboring dermal mast cells 23 to induce expression of neutrophil chemoattractants such as CXCL8. In this way, UV-induced IL-33 acts as a novel endogenous danger signal mediating the recruitment of innate immune cells to sites of infection or cellular damage.…”
Section: Discussionmentioning
confidence: 93%
“…20 IL-33 (IL-33/IL-1F11/NF-HEV) is a member of the IL-1 family of cytokines. 21,22 IL-33 exerts its biological function by binding to the ST2 receptor on the surface of T-helper 2 (Th2) cells, 22 mast cells, 22,23 basophils, 24 eosinophils, 25 NKT cells, 26 dendritic cells, 27 and neutrophils. 28 Similar to the effects of UV, IL-33 has potent immunemodulating properties that are mediated by the induction of cytokines including IL-1, -4, -6, -10. and -13, as well as chemokines such as CXCL8, CCL2, CCL3, and CCL5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 As a nuclear factor, the intracellular functions of IL-33 remain to be further clarified, although overexpression studies suggested a role as a transcriptional repressor. 10 As an extracellular cytokine, binding of IL-33 to the ST2 receptor activates nuclear factor-kB and mitogen-activated protein kinases, [3][4][5]11 and is involved in the polarization of T cells towards the Th2 cell phenotype 2,6,7,[11][12][13][14] and in activation of mast cells, [15][16][17][18][19][20] bosophils, 14,[20][21][22][23][24] eosinophils, [24][25][26] and natural killer cells. 14,27 IL-33 must be present extracellularly in order to play the crucial role in inflammatory, infectious and autoimmune diseases including anaphylactic shock, asthma, rheumatoid arthritis, atherosclerosis, systemic sclerosis and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%